2017
DOI: 10.1186/s12985-017-0857-7
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic, antigenic and biological characterization of pigeon paramyxovirus type 1 circulating in China

Abstract: BackgroundFor many years, ND has been one of the most important infectious pigeon diseases in China. In recent years, a high mortality has been observed in ND-infected pigeons in China. Mortality is from 40% to 80% or 100% in some cases.MethodsThe full-length genomes of four pigeon paramyxovirus type 1 (PPMV-1) strains, which were isolated from infected pigeons in China in 2012 and 2013, were sequenced and analyzed to determine the phylogenetic characteristics of PPMV-1 circulating in pigeons of China in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
(65 reference statements)
2
19
0
Order By: Relevance
“…The cross-reactivity HI assay showed that the R value between the GZ08 strain and the commonly used vaccine LaSota was 0.59, indicating a minor antigenic difference between LaSota and GZ08. The results were similar to those of previous research [24,34]. A large number of reports confirmed that antigen matching between vaccine and epidemic strains could increase the effectiveness of vaccines against epidemic strains [51][52][53][54].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cross-reactivity HI assay showed that the R value between the GZ08 strain and the commonly used vaccine LaSota was 0.59, indicating a minor antigenic difference between LaSota and GZ08. The results were similar to those of previous research [24,34]. A large number of reports confirmed that antigen matching between vaccine and epidemic strains could increase the effectiveness of vaccines against epidemic strains [51][52][53][54].…”
Section: Discussionsupporting
confidence: 90%
“…PCR amplification was performed using 12 pairs of overlapping primers specific to the complete genomes of NDV, as described previously [23]. To determine the 3and 5 -ends of the viral genomes, rapid amplification of cDNA end (RACE) was carried out using SMARTer™ RACE cDNA, as reported previously [24]. The PCR products were cloned into pMD19-T and sequenced at Sangon Biotechnology (Guangzhou, China).…”
Section: Sequence Analysismentioning
confidence: 99%
“…Epidemiological analysis has revealed that most ND outbreaks in chickens are associated with genotype VII NDVs (Qin et al, ; Zhu et al, ). In contrast, ND outbreaks in pigeons are always related to pigeon paramyxovirus type 1 (PPMV‐1), which belongs to genotype VI (Guo et al, ; Qiu et al, ). The virulent genotype IX NDVs were first identified in China and have been occasionally isolated from wild birds and waterfowl (Liu et al, ; Xiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the phylogenetic relationships between the isolates in this study with previously characterized NDV strains from different parts of world, full‐genome sequences were acquired from GenBank (http://www.ncbi.nlm.nih.gov/) for each known genotype of NDV (Qiu et al., ). All sequences were aligned and analysed using the ClustalW multiple alignment algorithm in the MegAlign program of the DNASTAR software suite (version 3.1; DNAstar, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%